Prime Minister's Decree No. 991 of the year 2023 Amending Certain Provisions of the Executive Regulations of the Law on Public Business Sector Companies Promulgated by Decree of the Prime Minister No. 1590 of the year 1991 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic